Análise da reestruturação imobiliária no município de Serra (ES) : estudo de condomínios industriais - Bassani, Izabela Dolores Cebin (2016)
This study aims to analyze the industrial condominiums in the city of Serra (ES), these are considered the new real estate developments, and in its particular way of reproduction, they perform a prominent part for the new role of the real estate market, as products and also components of the current urban restructuring process. Industrial condominiums are contemporary real estate products that shelter in its internal arrangement industries and other forms of reproduction of capital. They are products of a new phase of the city's production which negates the old form (centerperiphery) and emphasizes the production of new centers, resulting in the spreading of the urban fabric. The area chosen for the survey about the condominiums analyzed was the city of Serra, council member of the Metropolitan Region of Vitória (RMGV) and important spatial component of this urban restructuring from metropolitan area. The results show that the industrial condominiums in Serra, are more than a new real estate product, above all, they mark a period where the municipal government gives priority in their policies to real estate production favoring this niche of the productive sphere to the progressive practice of monopoly prices on the city space.